The Effectiveness of Dry Needling on Dimensions and Elastic Modulus of the Nasolabial Fold due to Aging Process: An Uncontrolled before-after Clinical Trial Study - Parinaz Omidi; Roya Ravanbod; Manizheh Mokhtari-Dizaji; Ghazi Sarhan (Vesnu Publications, 2020)
Introduction: Biomechanical properties of the skin change with pathological conditions and aging process. Nasolabial fold (NLF) is a degenerative manifestation of the skin tissue, which facilitates biomechanical properties measurement due to its quantifiable scales. The aim of this study was to evaluate the effectiveness of dry needling on decreasing NLF dimensions and improving NLF skin biomechanical properties. Materials and methods: 11 women aged between 35-55 years with NLF class between 2-2.5 were selected for study, and received 7 sessions of dry needling treatment. Another group of young women between 20-30 years considered as control group and received no treatment. NLF depth and area, epidermis and dermis thickness, and young modulus of NLF skin were analyzed with high resolution ultrasonography and a custom-made forceguage. For reliability of sonographic data the interclass correlation coefficient, and for between and within group comparisons, independent and paired t tests were used, respectively. Results: NLF depth and area decreased significantly (P < 0.001). Moreover, epidermis and dermis thickness and young modulus increased significantly (P < 0.001). Conclusion: Dry needling induced decrease in depth and area, and improved biomechanical properties of the NLF, without any side effect.